Relationship between social support and fear of cancer recurrence among Chinese cancer patients: A systematic review and meta-analysis - Lu, Xianying; Wu, Chenxi; Bai, Dingxi; You, Qian; Cai, Mingjin; Wang, Wei; Hou, Chaoming; Gao, Jing (Frontiers in Psychiatry, 2023)
Background: To quantitatively analyze the association between social support (SS) and fear of cancer recurrence (FCR) by reviewing current evidence from observational studies. Methods: A comprehensive literature search was performed in nine databases from inception to May 2022. Observational studies that used both SS and FCR as study variables were included. Regression coefficient (β′) and correlation coefficient (r) were calculated with R software. Subgroup analysis was utilized to investigate the degree of the relationship between SS and FCR as well as the impact of various forms of SS on FCR in cancer patients. Results: Thirty-seven studies involving 8,190 participants were identified. SS significantly reduced FCR risk (pooled β′ = -0.27, 95% confidence interval (CI) = -0.364 to -0.172), with moderate negative correlations (summary r = -0.52, 95% CI = -0.592 to -0.438). Meta-regression and subgroup analysis showed that types of cancer and study type were the source of heterogeneity. However, types of SS (actual SS, perceived social support (PSS), and others), source of actual SS, and source of PSS were not significant moderators. Conclusions: To the best of our knowledge, this is the first systematic review and meta-analysis to quantitatively investigate the association between SS and FCR in Chinese cancer patients using β′ and r coefficients. The results re-emphasized that social workers should enhance the use of SS by cancer patients and establish a sound SS system by either implementing more relevant research or developing targeted policies. Based on meta-regression and subgroup analyses, moderators of the association between SS and FCR should also be studied closely as they may help identify patients in need. In addition, longitudinal research, as well as mixed research, should be conducted to more comprehensively explore the relationship between SS and FCR. Keywords: fear of cancer recurrence; social support; cancer; meta-analysis